ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS III SDN BELENDUNG KOTA TANGERANG - Dede Lipiah; Aam Amaliyah; Boy Dorahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the ability to understand mathematical concepts of class III students at SDN Belendung, Tangerang City. This research uses a qualitative descriptive research method. The subjects in this research were 6 third grade students, including students who had the ability to understand mathematical concepts in the high, medium and low categories. Data collection techniques use description test questions, interviews and documentation. Then the data was analyzed using the Miles and Huberman model analysis technique using 3 stages, namely data reduction, data presentation and drawing conclusions. The results of the research show that the ability to understand mathematical concepts of class III students at SDN Belendung, Tangerang City in simple fractions material has quite good ability to understand concepts. In the indicator restating a concept, the percentage result was 66.6% in the sufficient category. For the indicator of classifying objects according to certain properties in accordance with the concept, the percentage result was 66.6% in the sufficient category, for the indicator of classifying objects according to certain characteristics in accordance with the concept, the percentage result was 0% in the very poor category. For indicators that provide examples and non-examples, you get a percentage result of 50% in the sufficient category, and for indicators that present concepts in various forms of mathematical representation, you get a percentage result of 83.3% in the very good category.